2001
DOI: 10.1021/jp010823q
|View full text |Cite
|
Sign up to set email alerts
|

Study of the Extinction Dynamics of the Mercury Beating Heart Reaction in Acid Solution and in the Presence of γ-Radiation

Abstract: The dynamics of the oscillatory mercury beating heart (MBH) reaction in acid aqueous solution with Ce IV as the oxidizing agent was investigated. The reaction slowly runs down over a period of a few hours, until all oscillatory activity eventually ceases. During this period the dynamics slowly evolves, showing qualitatively different forms of oscillations. These oscillations display different modes of oscillations with geometric structures similar to heart, circle, pentagon, hexagon, and 8-and 16-pointed stars… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 11 publications
0
17
0
Order By: Relevance
“…They deduced that the reason of oscillation was attributed to the change of surface tension caused by charge density difference. Castillo-Rojas et al 3 found that the mercury drop in aqueous solution with Ce IV could demonstrate different oscillation modes, such as circle, pentagon, hexagon, and 8-and 16pointed stars, resulting from a dynamic voltage produced in the chemical reaction. When an external power was supplied, Olson et al 4 showed that the oscillation mode could be sustained and altered from breather to 2-, 3-and 4-fold.…”
Section: Introductionmentioning
confidence: 99%
“…They deduced that the reason of oscillation was attributed to the change of surface tension caused by charge density difference. Castillo-Rojas et al 3 found that the mercury drop in aqueous solution with Ce IV could demonstrate different oscillation modes, such as circle, pentagon, hexagon, and 8-and 16pointed stars, resulting from a dynamic voltage produced in the chemical reaction. When an external power was supplied, Olson et al 4 showed that the oscillation mode could be sustained and altered from breather to 2-, 3-and 4-fold.…”
Section: Introductionmentioning
confidence: 99%
“…The signals (electrode potentials) are recorded between the Pt wires and Fe nails using the data acquisition control card (DAQ measurement computing USB-1616HS-4, 1000 Hz) with a computer interface. The details of the underlying nonlinear dynamics and chemistry of the regular and chaotic MBH oscillator can be found in the relevant literature [26][27][28][29][30][31][32][33] . Specifically, we consider the MBH oscillators in the parameter range that has been shown to yield chaotic dynamics 32 .…”
Section: Experimental Demonstration Of Asymmetry Induced Chaos Supprementioning
confidence: 99%
“…According to Keizer et al, 2,3 surface tension changes result from the formation and removal of a mercury sulfate film on the mercury surface in acid solution. The most complete chemical mechanism was proposed by Castillo-Rojas et al; 9 in their work they study the MBH system in acid solution with Pt as WE, iron as CE, and saturated calomel electrode as RE. Their proposed mechanisms consider different oxidizing agents for Hg 0 depending to their oxidizing strength.…”
Section: ■ Experimental Setupmentioning
confidence: 99%
“…The most complete chemical mechanism was proposed by Castillo-Rojas et al. ; in their work they study the MBH system in acid solution with Pt as WE, iron as CE, and saturated calomel electrode as RE. Their proposed mechanisms consider different oxidizing agents for Hg 0 depending to their oxidizing strength.…”
Section: Experimental Setupmentioning
confidence: 99%